2023
DOI: 10.31943/mathline.v8i1.350
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Using Android-Based Interactive Learning Media Development Results With The Assistance of Smart Apps Creator (SAC) on Social Aritmatic Materials

Abstract: This study aims to: determine the effectiveness of the use of instructional media, and determine the practical effect of using instructional media on student learning outcomes. The research method used is descriptive quantitative which aims to describe the practicality of using learning media, the effectiveness of using learning media, and the effect of using learning media on student learning outcomes. The analysis technique used in this study to determine the effect of the practicality of using instructional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…Studies have shown SAC's potential in improving learning outcomes across different subjects. For instance, SAC has been successfully implemented in physical education, math, and Arabic language teaching, demonstrating its versatility (Adhiono & Purnomo, 2021;Romdhoni, Agustina & Ayuningtyas, 2023;Abidin & Arifin, 2021). Despite these successes, there is a lack of comprehensive research on SAC's effectiveness in vocabulary acquisition in ELT, particularly for younger students.…”
Section: Introduction *mentioning
confidence: 99%
“…Studies have shown SAC's potential in improving learning outcomes across different subjects. For instance, SAC has been successfully implemented in physical education, math, and Arabic language teaching, demonstrating its versatility (Adhiono & Purnomo, 2021;Romdhoni, Agustina & Ayuningtyas, 2023;Abidin & Arifin, 2021). Despite these successes, there is a lack of comprehensive research on SAC's effectiveness in vocabulary acquisition in ELT, particularly for younger students.…”
Section: Introduction *mentioning
confidence: 99%